Analisis Metode Mengajar dalam Meningkatkan Minat Belajar Siswa Madrasah Aliyah Asy-Syafi’iyyah Karangasem Margasari - Nurbaety, Merfi; Cato; Satria Wicaksono, Akrom; Mas'udi, Ali; Fakhriyah, Nada; Selnistia, Rizki (CV Kalimasada Group, 2024)
The purpose of this study is to find out how students' perceptions of learning methods affect their interest in learning. This study is a qualitative research conducted at MA Asy-Syafi'iyyah with students as the object of research. Data were collected through participatory observation and in-depth interviews. The results show that teachers who use monotonous and unvaried learning methods significantly affect students' interest in learning. Students who are engaged and motivated in the learning process have a high interest in learning, while students who are bored and unchallenged by the methods used tend to lose their interest in learning. Teachers' learning methods greatly influence students' interest in learning. By using innovative, interesting and engaging methods, students are more interested in learning and their interest increases.